Analysis of the TGT (Games, Games, and Tournament) Model on Aqidah Learning Outcomes in Elementary Schools - Alyza Zulfa; Iqbal Amar Muzaki; Afiyatun Kholifah (al-Afkar, Journal For Islamic Studies, 2026)
Education will enable students to develop understanding, attitudes, and character, including in religious matters. At the elementary school level, Aqidah lessons are the primary foundation for instilling moral and spiritual values. Therefore, a learning method is needed that not only conveys the material but also makes it easier for students to understand and internalize it. One model that is considered effective is Teams, Games, and Tournaments (TGT). This model combines group work, educational games, and tournaments to encourage learning enthusiasm and improve student academic achievement. The aim was to determine the extent to which the TGT model influences Aqidah learning. The results of the study showed enthusiasm and motivation during the student learning process. They more easily understood Aqidah material through group discussions, fun games, and tournaments that encouraged learning enthusiasm in a healthy competitive atmosphere. Compared to conventional methods, the TGT model was able to create more engaging and interactive learning.